Development of Teaching Materials Based on Scientific Argumentation on the Topic of Earth and Solar System - Farida Nur Setiati; Siswanto Siswanto; Eko Juliyanto; Eli Trisnowati; Firmanul Catur Wibowo (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Scientific argumentation plays a crucial role in fostering higher-order thinking and scientific literacy in science education. However, studies have shown that Indonesian students’ scientific argumentation skills remain low, while existing science textbooks generally reach only level 2 of argumentation quality. Consequently, these materials are not yet effective in facilitating the development of students’ argumentation competence. Furthermore, the topic of the Earth and the Solar System continues to generate misconceptions among students, highlighting the need for learning materials that integrate structured argumentation activities. This study, therefore, aims to develop science teaching materials based on scientific argumentation activities for the topic of the Earth and the Solar System. The research employed the Fuzzy Delphi Method, encompassing five key stages: (1) determining the model of scientific argumentation construction for developing argumentative texts, (2) defining learning indicators for material development, (3) designing teaching materials based on expert-validated indicators, (4) assessing the readability of the materials, and (5) validating the developed materials. The findings indicate that the resulting teaching materials are valid and appropriate for students’ cognitive levels. The materials were structured using a scientifically validated argumentation model and learning indicators categorized into cognitive levels of remembering, understanding, analyzing, and creating across five subtopics. Readability analysis using the Fry graph confirmed suitability for the target age group, while expert validation demonstrated high content and construct validity. These results suggest that the developed materials effectively support the integration of scientific argumentation in science learning, particularly on Earth and Solar System concepts.Keywords: scientific argumentation, teaching materials, earth and solar system, fuzzy delphi method.